ANALISIS KOGNISI SOSIAL DAN KONTEKS SOSIAL PADA LAGU MENTERI DURMAGATI - Farhana Cahya Amalina Widagdo; Hotma Simanjuntak; Patriantoro Patriantoro; Intan Yustina (ASMARALOKA : Jurnal Bidang Pendidikan, Linguistik dan Sastra Indonesia, 2026)
This study aims to describe social cognition and social context in the song “Menteri Durmagati” by Andry Deblenk based on the Critical Discourse Analysis model developed by Teun A. van Dijk. This study employs a qualitative method using a Critical Discourse Analysis approach focused on aspects of social cognition and social context. The research data consists of the lyrics of the song “Menteri Durmagati,” while data collection was conducted through the listen-and-note technique. Data analysis was performed by identifying, classifying, and describing the forms of social cognition and social context contained within the song’s lyrics. The research findings indicate that, regarding social cognition, the songwriter presents a critical perspective on corrupt officials who are power-hungry, fond of image-building, engage in nepotism, and abuse their positions for personal gain. The author also demonstrates an understanding of organized corruption practices, budget manipulation, weak legal oversight, and the hedonistic culture of the political elite. Meanwhile, regarding the social context, the song portrays societal conditions marked by bureaucratic corruption, a culture of collective corruption, poor development quality, the phenomenon of officials’ self-promotion on social media, nepotism, and weak law enforcement. The use of Javanese ngoko, humor, satire, and wayang symbols makes the social critique in the song more relatable to the public and easy to understand. Thus, the song “Menteri Durmagati” serves not only as entertainment but also as a medium for social criticism that reflects the public’s concerns regarding the abuse of power and the moral conduct of public officials.